2021
DOI: 10.1080/17453674.2021.1941629
|View full text |Cite
|
Sign up to set email alerts
|

No change in reoperation rates despite shifting treatment trends: a population-based study of 4,070 proximal humeral fractures

Abstract: 2021): No change in reoperation rates despite shifting treatment trends: a population-based study of 4,070 proximal humeral fractures, Acta Orthopaedica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A Swedish single-center study of 4,070 PHF reported an average proportion of surgically treated fractures (2011–2017) of 23%. Among the operated cases, the proportion of locking plates decreased from 47% to 25% while the proportion of RSA increased from 2% to 19% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Swedish single-center study of 4,070 PHF reported an average proportion of surgically treated fractures (2011–2017) of 23%. Among the operated cases, the proportion of locking plates decreased from 47% to 25% while the proportion of RSA increased from 2% to 19% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bergdahl et al ( 35 ) demonstrated problems with coding in the Swedish National Patient Registry. However, the DNPR differs from the Swedish National Patient Registry in several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Due to thinning trabeculae and cortical bones, severely displaced and comminuted PHFs with medial calcar impaction are common injuries and are normally treated using a locking plate or intramedullary nail internal fixation ( Mease et al, 2021 ). Unfortunately, complications, such as a loss of reduction and internal fixation failure, and functional limitations occurred in approximately 40% of patients who underwent surgery, and the reoperation rate was 19.7% ( Barlow et al, 2020 ; Bergdahl et al, 2021 ). Increasing the mechanical stability of the medial column and counteracting varus displacement force may be useful to avoid those complications ( Euler et al, 2017 ; Dasari et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, with the increasing performance of shoulder arthroplasty procedures, also the risk of complications such as periprosthetic joint infection is heightened. A few studies reported revision rates based on large registry data such as the Nordic Arthroplasty Register Association [14][15][16], the Swedish Fracture Register [17] and the Australian Orthopaedic Association National Joint Replacement Registry [18]. However, substantial heterogeneity among studies reporting reoperation rates was noted [19].…”
Section: Introductionmentioning
confidence: 99%